Financial Technology Innovation (Fintech) and Financial Industry Transformation in Manufacturing Companies - Wardani, Mega Suciati (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
The transformation of financial technology (Fintech) has played a crucial role in transforming the manufacturing industry in Indonesia. Fintech provides innovative solutions to overcome traditional financial challenges, improve operational efficiency, and expand access to capital. However, Fintech adoption in the sector also faces various challenges, including data security, regulatory uncertainty, and technology disparity. This study aims to analyse the challenges and impacts of Fintech adoption on the manufacturing industry in Indonesia, as well as identify the factors that influence such adoption. This research uses a qualitative approach by conducting a literature review of relevant articles from 2019 to 2023. Data was analysed to identify trends, challenges, and impacts of Fintech adoption on the manufacturing sector. The results show that Fintech has provided significant benefits to the manufacturing industry, such as improved operational efficiency and wider access to capital. However, challenges such as data security and regulatory uncertainty are still major barriers to Fintech adoption. Fintech is an important catalyst for the transformation of the manufacturing industry in Indonesia. To maximise its benefits, there needs to be a concerted effort between the government, regulators, and industry players to overcome existing challenges and create a conducive environment for Fintech adoption.